Limitation of the constitutional rights and freedoms of a person and a citizen in connection with the military aggression of the russian federation - Shevchuk L. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Goal. This article focuses on the norms and provisions of the constitution of Ukraine, which regulate the rights and freedoms of a person and a citizen, which can be limited during the period of martial law, in particular, today, unjustifiably and brazenly provoked by the russian federation. Also, the legal grounds for their introduction are considered, as legal steps to protect the interests of the state as a whole, as well as the consequences arising from these introductions. Method. The analysis and generalization of the scientific and theoretical material was carried out. In the process of research, such methods of scientific knowledge as comparative, systemic and structural were observed. Results. In the course of this study, an analysis of the application of restrictions on the constitutional rights and freedoms of a person and a citizen in connection with the military aggression of the russian federation, as well as the effect of these restrictions on the ordinary life of an ordinary Ukrainian, their effectiveness in relation to the security of the state as a whole, was carried out. Scientific novelty. Taking into account the fact that Ukraine, as a sovereign state, for the first time since the declaration of independence, can apply such legal steps, which directly affect the rights and freedoms of a person and a citizen, in particular in their limitation, which became the basis due to the military invasions of the Russian Federation, and therefore, it is appropriate to emphasize that this issue is quite relevant today. Practical significance. The results and conclusions of scientific research can be applied or taken into account in law enforcement practice, consulting. Practical significance. The results and conclusions of scientific research can be applied or taken into account in law enforcement practice, consulting.